2010
DOI: 10.1016/j.idairyj.2009.11.004
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic, genetic and technological characterization of Lactococcus garvieae strains isolated from a raw milk cheese

Abstract: a b s t r a c tA series of Lactococcus garvieae strains isolated as the majority population of a Spanish traditional, starter-free cheese made from raw milk were phenotypically and genotypically characterised to address their biochemical potential, safety requirements, and technological properties. As expected, all L. garvieae cheese strains fermented lactose but grew slowly in UHT-treated milk. Enzymatic activities of L. garvieae were similar to those of Lactococcus lactis, although higher esterase and lipase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 34 publications
0
34
0
Order By: Relevance
“…Some L. garvieae strains may also be major components of the autochthonous microbial populations of certain artisanal cheeses (5). In fact, it is believed that the activity of L. garvieae strains may contribute to the final sensory characteristics of some dairy products (54). The adaptation of L. garvieae to the milk environment was likely enabled by the acquisition of certain plasmids (55).…”
Section: Discussionmentioning
confidence: 99%
“…Some L. garvieae strains may also be major components of the autochthonous microbial populations of certain artisanal cheeses (5). In fact, it is believed that the activity of L. garvieae strains may contribute to the final sensory characteristics of some dairy products (54). The adaptation of L. garvieae to the milk environment was likely enabled by the acquisition of certain plasmids (55).…”
Section: Discussionmentioning
confidence: 99%
“…The identified strains of S. thermophilus in the latter cheese have been isolated and are currently being characterised and compared with industrial starter strains (unpublished). Similarly, L. garvieae, a lactic acid bacterium similar to L. lactis (Fernández et al 2010), has been identified by culturing and molecular methods in other cheese types (Alegría et al 2009;Flórez and Mayo 2006).…”
Section: Discussionmentioning
confidence: 99%
“…During the last decades, lots of approaches have been introduced under culture independent molecular methods which are frequently used in the identification and characterization purposes of L. lactis such as Culture-Independent Polymerase Chain Reaction (Salbi et al, 2014;) 16S rDNA Sequencing (Aquilanti et al, 2007;Khemariya et al, 2013b), PCR-Denaturing Gradient Gel Electrophoresis (PDGE) (Mrkonjić Fuka et al, 2010;Pogačić et al, 2010;Marui et al, 2015;), PCR-Temporal Temperature Gradient Electrophoresis (TTGE) (ElBaradei et al, 2008), Single-Strand Conformation Polymorphism-PCR (SSCP-PCR) (Saubusse et al, 2007), Real Time PCR (qPCR) (Grattepanche et al, 2005;Ruggirello et al, 2014), Fluorescence in situ Hybridization (FISH) (Miks-Krajnik and Babuchowski, 2014), Amplified Ribosomal DNA Restriction Analysis (Partial ARDRA) (Delgado and Mayo, 2003), Length Heterogeneity PCR (LH-PCR) (Brusetti et al, 2006), Multilocus Sequence Analysis (MLSA) (Rademarker et al, 2007;Khemariya et al, 2012) (GTG) 5 -PCR Fingerprinting (Rademarker et al, 2007;Khemariya et al, 2014), PCR-Restriction Fragment Length Polymorphism (PCR-RFLP) (Deveau et al, 2003;Khemariya et al, 2013b), Multiple Locus Minisatelite Typing (MLVA) (Que'ne'e et al, 2005), RAPD-PCR (Randomly Amplified Polymorphic DNA-PCR) (Samaržija et al, 2002), Pulse Field Gel Electrophoresis (PFGE) (Campo et al, 2002), Repetitive Element Sequence based PCR (Rep-PCR) (Fernandez et al, 2010), Comparative Genomic Hybridization (CGH) (Taibi et al, 2010), Nested PCR (Khemariya et al, 2013c), Multiplex PCR (Pu et al, 2002) and Sau-PCR (Corich et al, 2005).…”
Section: Enumeration Of L Lactismentioning
confidence: 99%